2019
DOI: 10.1038/s41467-019-12362-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the coordination structure of single-atom Fe-NxCy catalytic sites for benzene oxidation

Abstract: Atomically dispersed metal-N-C structures are efficient active sites for catalyzing benzene oxidation reaction (BOR). However, the roles of N and C atoms are still unclear. We report a polymerization-regulated pyrolysis strategy for synthesizing single-atom Fe-based catalysts, and present a systematic study on the coordination effect of Fe-NxCy catalytic sites in BOR. The special coordination environment of single-atom Fe sites brings a surprising discovery: Fe atoms anchored by four-coordinating N atoms exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
291
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 387 publications
(308 citation statements)
references
References 51 publications
17
291
0
Order By: Relevance
“…It is also presumed that the N at the di‐vacancies may help to attract M atoms due to the extra electron pair at d orbital, forming more M‐N 4− x C x structures thus proving more active sites for electrocatalysis. In summary, di‐vacancy is necessary as a home to accommodate M atoms; N atoms may play the key role to enhance the reactivity of M‐N 4− x C x active site (with a suitable coordinated N) and form a high number of such active sites.…”
Section: Introductionmentioning
confidence: 99%
“…It is also presumed that the N at the di‐vacancies may help to attract M atoms due to the extra electron pair at d orbital, forming more M‐N 4− x C x structures thus proving more active sites for electrocatalysis. In summary, di‐vacancy is necessary as a home to accommodate M atoms; N atoms may play the key role to enhance the reactivity of M‐N 4− x C x active site (with a suitable coordinated N) and form a high number of such active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the coordination effect of active sites can considerably affect their electronic structures, subsequently tuning their electrocatalytic activity. [31][32][33] These pioneering studies have inspired us to modulate the local environment of Ru SA for improved trifunctional electrocatalytic performance, which has not been explored before, however.…”
mentioning
confidence: 99%
“…Some catalytic properties of SACs are even higher than that of commercial catalysts. Apart from above electrochemical reactions, carbon‐based SACs have begun to be used in many photocatalysis organic synthesis, and versatile biomedical applications, [ 108,109 ] for example, Pd‐NC SACs (single‐atom Pd on N‐doped graphene) show high selectivity in photothermal hydrogenation of acetylene to ethylene; [ 110 ] Fe‐NC SACs (Fe‐N x C y catalytic sites on carbon) have high activity and selectivity in catalytic oxidation of benzene to phenol [ 62 ] and Zn‐NC SACs (single‐atom Zn on N‐doped carbon) can suppress the bacteria proliferation and facilitate the wound regeneration due to their predominant peroxidase‐mimicking activity. [ 111 ] However, there is no doubt that there is always great potential for the development of carbon‐supported SACs, which raises a question of how to effectively and accurately regulate metal catalytic sites for preparing low‐cost SACs with high activity, stability, and selectivity.…”
Section: The Prospective For Modified Carbon‐based Sacsmentioning
confidence: 99%
“…[ 51,52 ] The other is to regulate heteroatoms coordination on carbon supports, which derive from the widely researched modification of carbon materials by multiple heteroatom doping. Carbon defects or vacancies can act as coordinating sites through M–π interactions [ 113 ] and changing the number of NM bonds [ 60,62 ] also regulates the electronic structure of the metal site. Nevertheless, the weak M–π interactions or few NM bonds of single metal atoms may lead to the appearance of metal aggregation during the long‐term catalytic reaction.…”
Section: The Prospective For Modified Carbon‐based Sacsmentioning
confidence: 99%
See 1 more Smart Citation